Identification of components from Aralia elata and their effects on muscle health and gut microbiota - Ko, Hyejin; Bekele, Tigist T.; Le, Tam Thi; Cha, Kwang Hyun; Kim, Subeen; Youn, Hye-Young; Jung, Sang Hoon; Kim, Myungsuk (Elsevier BV, 2024)
Aralia elata, a medicinal and edible plant, has a well-known culinary history. However, its detailed phytochemical profile and effects on muscle health and the gut microbiota are still unexplored. We investigated the protective properties of A. elata water extract (AE) against muscle atrophy and identified bioactive compounds, including a novel one, responsible for AE-mediated effects. AE promoted protein synthesis pathways and suppressed protein degradation markers, enhancing energy production by increasing glutathione, ATP levels, and mitochondrial biogenesis. AE phenolic components selectively affected specific pathways; catechol targeted protein degradation, ethyl catechol enhanced protein synthesis and reduced oxidative stress, and methyl dihydrocaffeate promoted mitochondrial biogenesis and ATP production. In mice, AE improved muscle mass and exercise capacity. These benefits were attributed to altered gut microbiota composition, specifically of Erysipelatoclostridium, Anerotruncus, and Clostridia vadinBB60, with muscle atrophy-related traits. Collectively, AE could be developed as a food supplement for muscle health.